Writing For Visual Media - Friedmann, Anthony (Woburn, Ma Focal Press, 2001)
Writing for Visual Media focuses on the fundamental problems faced by writers beginning to create content for media that is to be seen rather than read. This book takes the student from basic concepts to a first level of practice through an explicit method that trains students to consistently identify a communications problem, think it through, and find a resolution before beginning to write. Through successive exercises, it helps them acquire the skill and confidence they need to write effective films, corporate and training videos, documentary, ads, PSAs, tv series and other types of visual narrative. Writing for Visual Media also has a chapter on writing for interactive media, including promotions, instructional programs, and games.
Includes Index
Keywords: Mass media--Authorship